Efektivitas Bimbingan Kelompok Dengan Teknik Self Talk Untuk Meningkatkan Konsep Diri Siswa Kelas VIII MTs Masyariqul Anwar Caringin - Septi Nurdiana; vasco delano; Devi Nurul Fikriyani (Universitas Mathla'ul Anwar Banten, 2026)
Effectiveness of Group Guidance using Self-talk Techniques to Improve Students' Self-Concept (Quasi Experiment on Class VIII Students at MTs Maisyairiquil Ainwair Cairingin Academic Year 2023/2024).This research aims to find out the general picture of the self-concept of MTs Maisyairiquil Ainwair Cairingin class students for the 2023/2024 academic year, as well as to find out the effectiveness of group guidance using self-talk techniques to improve students' self-concept. The research was carried out using the quantitative method of nonequivalent control group design model from a population of 150 students with a sample of 24 students. Data analysis used in this research used the normality test, homogeneity test and paired sample t test, by comparing two group members, namely the experimental group and the experimental group. control. Both groups were given a pre-test and post-test, however the experimental group was given group guidance treatment and the control group was given no treatment. The research results showed that after being given treatment there was a difference in the average pre-test and post-test scores with an increase above a score of 79. The research results can be concluded that group guidance using the self-talk technique is effective for improving students' self-concept.